HUBUNGAN TINGKAT PENGETAHUAN, SIKAP, DAN KEPATUHAN MINUM OBAT TERHADAP PENGENDALIAN TEKANAN DARAH PASIEN HIPERTENSI USIA 15-64 TAHUN DI PUSKESMAS KECAMATAN MAKASAR TAHUN 2022 - Raden Roro Ariesna Muharany (2023)
Hypertension is a noncommunicable disease, the biggest cause of death, and DKI Jakarta province has the highest prevalence at 13.4%. Incidence of hypertension in the Makasar Subdistrict Health Center reached 4,986 cases in January to October 2022. There are 3 factors to be examined: knowledge, attitudes, and medication adherence. The research aim is to determine the relation between knowledge level, attitude, and medication adherence to blood pressure control in hypertensive patients aged 15-64 years at the Makasar Subdistrict Health Center in 2022. This study used a cross-sectional design with a sample of 71 respondents was taken by consecutive sampling technique. Statistical analysis used the chi-square test with (α = 0,05). The results showed that there was a relation between knowledge (p-value = 0,04; OR = 37,200; 95%CI = 3,243 - 426,674), attitude (p-value = 0,022; OR = 15,273; 95%CI = 1.451 - 160.732), and medication adherence (p-value = 0,028; OR = 13,750; 95%CI = 1,314 - 143,852) on blood pressure control in hypertensive patients aged 15-64 years at the Makassar Subdistrict Health Center in 2022. There is a significant relation between the level of knowledge, attitudes, and medication adherence to blood pressure control in hypertensive patients aged 15-64 years.